Targeting the Enhanced Sensitivity of Radiotherapy in Cancer: Mechanisms, Applications, and Challenges - Yuanyuan Zhao; Fangqin Tan; Jiajia Zhao; Shuchang Zhou; Yao Luo; Chen Gong (MedComm)
ABSTRACT Cancer is a major public health, societal, and economic challenge worldwide. According to Global Cancer Statistics 2022, it is estimated that by 2050, there will be 35 million new cancer cases globally. Although patient survival rates have improved through various therapeutic approaches, including surgery, chemotherapy, and radiotherapy, treatment efficacy remains limited once tumor metastasis occurs. Among various cancer treatment strategies, radiotherapy plays a crucial role. Along with surgery and chemotherapy, radiotherapy is a cost‐effective single‐modality treatment, accounting for approximately 5% of total cancer care costs. The use of radiosensitizing agents such as histone deacetylase inhibitors, 2‐deoxy‐d‐glucose, enterolactone, and squalene epoxidase can enhance radiotherapy effectiveness. Recent radiosensitization methods involve physical stimuli and chemical radiosensitizers. However, improving their efficacy, durability, and overcoming radioresistance remain significant challenges. This review first introduces current applications of radiotherapy in cancer treatment, the molecular mechanisms underlying its anticancer effects, and its side effects. Second, it discusses the main types of radiosensitizers, their latest applications, and recent challenges in cancer treatment. Finally, it emphasizes on clinical trials of radiosensitizing agents and explores potential biomarkers for radiotherapy response in cancer. Multifunctional nanoparticles have shown greater clinical applicability than single‐functional nanoparticles. Future research will focus on enhancing the drug‐carrying capacity of nanomaterials to further improve radiotherapy outcomes.